2022
DOI: 10.1002/smll.202105513
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Decarbonylation Mechanisms in the Atomic Layer Deposition of High‐Quality Ru Films by Zero‐Oxidation State Ru(DMBD)(CO)3

Abstract: Achieving facile nucleation of noble metal films through atomic layer deposition (ALD) is extremely challenging. To this end, η 4 -2,3-dimethylbutadiene ruthenium tricarbonyl (Ru(DMBD)(CO)3), a zero-valent complex, has recently been reported to achieve good nucleation by ALD at relatively low temperatures and mild reaction conditions. We study the growth mechanism of this precursor by in situ quartz-crystal microbalance and quadrupole mass spectrometry during Ru ALD, complemented by ex situ film characterizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
(209 reference statements)
0
2
0
Order By: Relevance
“…In one example of this type of experiments, the ALD of copper films using copper(I)-N,N ′ -diisopropylacetamidinate ([Cu(iPr 2 -amd)] 2 ) and a hydrogen plasma was inferred, on the basis of the QCM measured mass loss during the uptake of the metal precursor, to involve the partial decomposition of the Cu precursor to produce isopropyl and N-isopropylacetamidinate fragments [52]. In a second study, QCM measurements were used to propose that the deposition of ruthenium films using η 4 -2,3-dimethylbutadiene-ruthenium(0)-tricarbonyl ((H 2 C=C(CH 3 )C(CH 3 )=CH 2 )Ru(CO) 3 ) follows a kinetically limited decarbonylation reaction, a non-self-limiting step that brings about some challenges to the implementation of the film growth process in ALD mode [53]. QCM data were also used to conclude that during the ALD of chromium oxide films using chromium(III)-2,4-pentanedionate (also called chromium(III)-acetylacetonate, Cr(acac) 3 ) and ozone O 3 there is the risk of inducing an etching pathway due to the partial surface oxidation of the Cr 2 O 3 with excess ozone [54].…”
Section: Mechanistic Studies Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In one example of this type of experiments, the ALD of copper films using copper(I)-N,N ′ -diisopropylacetamidinate ([Cu(iPr 2 -amd)] 2 ) and a hydrogen plasma was inferred, on the basis of the QCM measured mass loss during the uptake of the metal precursor, to involve the partial decomposition of the Cu precursor to produce isopropyl and N-isopropylacetamidinate fragments [52]. In a second study, QCM measurements were used to propose that the deposition of ruthenium films using η 4 -2,3-dimethylbutadiene-ruthenium(0)-tricarbonyl ((H 2 C=C(CH 3 )C(CH 3 )=CH 2 )Ru(CO) 3 ) follows a kinetically limited decarbonylation reaction, a non-self-limiting step that brings about some challenges to the implementation of the film growth process in ALD mode [53]. QCM data were also used to conclude that during the ALD of chromium oxide films using chromium(III)-2,4-pentanedionate (also called chromium(III)-acetylacetonate, Cr(acac) 3 ) and ozone O 3 there is the risk of inducing an etching pathway due to the partial surface oxidation of the Cr 2 O 3 with excess ozone [54].…”
Section: Mechanistic Studies Experimental Approachmentioning
confidence: 99%
“…QCM studies may be complemented by analysis of the desorbing gasses in order to better correlate mass loses on the surface with the formation of stable gas-phase products. This analysis is typically carried out downstream from the ALD reactor [28,53,[56][57][58]. In a case where a solution of RuO 4 in a methyl-ethyl fluorinated solvent was used in conjunction with an alcohol to design an ALD process for the deposition of ruthenium dioxide films, mass spectrometry was used to determine that the RuO 4 •alcohol complex that adsorbs on the surface reacts to generate carbon dioxide while leaving a partially oxidized RuO x species, which gets incorporated in the growing film; there is then a time delay before the solvent (alcohol) desorbs from the surface [59].…”
Section: Mechanistic Studies Experimental Approachmentioning
confidence: 99%
“…Thin films have demonstrated great utility in tackling a variety of scientific challenges across a range of applications. In many of these contexts, specific material property, chemistry, and nanostructure needs have driven major developments in fabrication, with atomic layer deposition (ALD) having particular power to address requirements for precise, complex, and tunable materials. , While many idealized ALD reactions are presumed to take place in a self-limiting manner confined to only the growth surface, numerous deviations exist in real ALD systems; and thus comprehensive and detailed understandings of ALD growth processes are needed for effective implementation, particularly for precisely designed materials. , Many nonideal, complex chemistries have been described in ALD, , including a recent report of unexpected behaviors of oxygen species in iron oxide ALD using ozone . In that report, it was found that rather than the self-limiting formation of a submonolayer of surface-bound material at each half-cycle, greater than a monolayer of reactive oxygen species from ozone was incorporated subsurface into the film (the so-called "oxygen reservoir"), leading to a more complex mechanism of ALD growth.…”
Section: Introductionmentioning
confidence: 99%
“…9,13,14 While many idealized ALD reactions are presumed to take place in a self-limiting manner confined to only the growth surface, numerous deviations exist in real ALD systems, and thus comprehensive and detailed understandings of ALD growth processes are needed for effective implementation, particularly for precisely designed materials. 1,15 Many non-ideal, complex chemistries have been described in ALD, 14,[16][17][18][19][20] including a recent report of unexpected behaviors of oxygen species in iron oxide ALD using ozone. 21 In that report, it was found that rather than the self-limiting formation of a sub-monolayer of surface-bound material at each half cycle, greater than a monolayer of reactive oxygen species from ozone was incorporated subsurface into the film, leading to a more complex mechanism of ALD growth.…”
Section: Introductionmentioning
confidence: 99%